Odontaspis ferox ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Odontaspis ferox (Risso, 1810). Ragged-tooth Shark or Smalltooth Sandtiger Shark. To about 4.5 m (14.8 ft) TL (Ebert et al. 2013). Circumglobal in temperate waters; western Pacific Ocean north to Honshu Island, Japan (Yoshino and Aonuma in Nakabo 2002); Newport Beach and Santa Barbara Island, southern California (Seigel and Compagno 1986) to Gulf of California (Eschmeyer and Herald 1983), Colombia (Mejía-Falla et al. 2007); Islas Galápagos (Acuña-Marrero et al. 2013); Desventuradas Islands, Chile (Long et al. 2014). Depth: 10–1,015 m (33–3,329 ft) (min.: Ebert et al. 2013; max. Weigmann 2016). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 14, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...